Pengaruh Penambahan Larutan Asam Sitrat sebagai Acidifier pada Air Minum terhadap Profil Darah (Eritrosit, Hemoglobin, Hematokit) Ayam Kampung Unggul Balitnak (KUB) - Ningrum, Tiara Arnenda Diah; Septinova, Dian; Muhtarudin, Muhtarudin; Hartono, Madi (Department of Animal Husbandry, Faculty of Agriculture, University of Lampung, 2024)
This study aims to determine the effect of the addition of citric acid acidifier solution in drinking water on blood profile (Hemoglobin, Erythrocytes and Hematocrit or Packed Cell Volume (PCV) and to determine the supplementation level of citric acid acidifier solution up to a dose of 1.5% in drinking water for KUB chickens. The method used in this study was a completely randomized design (CRD) with 4 treatments and 5 replicates, namely P0; drinking water without the addition of citric acid (Control), P1; drinking water with the addition of 0.5% citric acid, P2; drinking water with the addition of 1% citric acid and P3; drinking water with the addition of 1.5% citric acid. Data were analyzed using analysis of variance with a level of 5% if the treatment is significantly different (P < 0.05) then tested further with the BNT test. The results showed that the addition of citric acid had a significant effect (P<0.05) on blood erythrocyte levels, but no significant effect (P>0.005) on blood hemoglobin levels and blood hematocrit levels. The conclusion from the research that has been done is that the provision of acidifier supplementation in the form of citric acid in drinking water up to a dose of 1.5% does not affect the amount of hematocrit and the amount of hemoglobin, but does affect the number of erythrocytes in KUB chickens aged 1–8 weeks.